Penggunaan Smart Contract Pada Transaksi E-Commerce Dalam Perspektif Hukum Perdata di Indonesia - Hesti Ayu Wahyuni; Yuris Tri Naili; Maya Ruhtiani (LPPM Universitas Harapan Bangsa, 2023)
One of the technological innovations in the industrial era 4.0 is the existence of smart contracts. Smart Contract is a further development of the application of blockchain after the existence of cryptocurrency, namely a computer program that is basically an electronic agreement in a blockchain database system with the aim of a protocol in carrying out an agreement or agreement between parties that can execute agreement clauses automatically. This article was examined using normative juridical research methods. Normative juridical research is research based on an analysis of legal norms, the sense of law as it is written in the books and statutes (in the literature and statutory regulations). The results of the study show that the use of smart contracts in e-commerce transactions in Indonesia has been implemented properly and when viewed from the perspective of Civil Law in Indonesia, the use of smart contracts in e-commerce transactions has fulfilled the elements of the agreement in general, although there are still deficiencies such as automatic execution as if made by one party only.